HEREDITARY FRUCTOSE INTOLERANCE IN A PEDIATRIC CONTEXT - Parente, Lucas Leimig Telles; Parente, Rodrigo Emmanuel Leimig Telles; Telles, Maria Valéria Leimig; Silva, Maria das Graças Nascimento (Amadeus International Multidisciplinary Journal, 2018)
Carbohydrate intolerance is relatively common in childhood, but its diagnosis and management are still quite precarious. Hereditary fructose intolerance (HFI) is an autosomal recessive disease that results in deficiency of the enzyme aldolase B, which contributes to the onset of gastrointestinal and metabolic symptoms, triggered by the ingestion of foods high in fructose, sucrose or sorbitol. Methodology: For the accomplishment of such a study a search of the literature was done from August to September of the year 2018 with publication period of a maximum of 10 years. The theoretical reference was elaborated through the collection of relevant scientific articles on the subject, made in the electronic databases: Scientific Electronic Library Online (SciELO), Pubmed, EBSCOhost and CAPES, from descriptors generated by DeCS: "Fructose Intolerance"; "Child" and its correspondents in English. Thus, 81 articles were obtained and, from the title of the literature and its abstracts, were used. 19 Ademias, articles that were related to the topics covered in this study or whose sample was not composed by humans were also discarded. The diagnosis of HFI is based on the suggestive clinical picture initiated after the ingestion of the fructose, sucrose and sorbitol already mentioned, associated with the use of invasive and noninvasive examinations, but the confirmation is based on the response to the improvement of the symptoms after the restriction of the ingestion of such food, which constitutes the best therapy. Conclusion: Based on the consequences of inadequate management of HFI, it is of fundamental importance that the affected children have an early diagnosis, associated with an adequate nutritional monitoring, which enables an improvement in the quality of life of these individuals, besides preventing important repercussions such as renal and hepatic impairment. Keywords: Hereditary Intolerance to Fructose, Child and Diet